Community Empowerment Through Family Counseling Concerning Current Parenting Patterns in Pangkalan Losarang Village, Indramayu - Tita Rizqiyah; Didik Himmawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The aim of this community service (PkM) is to provide education regarding the importance of increasing insight into current parenting patterns to be able to upgrade knowledge and increase insight into the impact of good parenting patterns on the future of children and families. Besides that. Several delivery methods in this supporting program are delivered face to face, interviews, discussions and briefings at the Pangkalan Village hall, documentation and evaluation. Obtain data in implementing supporting programs by analyzing data from activity results in the form of posttest and pretest. By involving several mothers in achieving program results in Pangkalan Village, it can produce a younger generation who are mentally healthier in living their daily lives. Some of the results of initial observations regarding the village's potential, there are several obstacles in implementing this support program, namely because there is no public awareness of the importance of good parenting patterns to support mental health in children. Therefore, we provide a forum for parents to continue to increase their knowledge. regarding parenting styles today. The result of this community service (PkM) is to increase insight into parenting patterns by bringing in experts who are truly involved in their field, it is hoped that this can produce a younger generation who is mentally healthier in living their daily lives.